VALUASI EKONOMI SUMBERDAYA PESISIR KOTA TERNATE (Suatu Studi Nilai Ekonomi Pesisir sebagai Moral Suation Dalam Usaha Menjaga dan Melestarikannya) - Anhar Drakel (Jurnal Pendidikan dan Ekonomi (JUPEK), 2021)
Ternate City is a coastal city, the existence of coastal resources needs to be well maintained for the survival of mankind. Management of coastal areas must be sustainable (sustainable development) and lead to renewable resources. The purpose of this study is as follows to determine the economic value of the coastal resources of Ternate City as one of the policy input factors in the economic valuation of coastal resources which has a very important role. The analytical method used in this study is the contingency valuation method. Based on the results of the study, The value of direct fishery benefits from coral reefs in Ternate City is Rp. 3,251,360,000./year, whereas. Thus the total direct benefit value of coral reefs in Ternate City is Rp. 3.251.360.000./year. The economic value of these coral reefs is still relatively small. This is because other potentials such as coastal tourism have not been utilized